Mechanical Sleeves in Substations - Viswanathan, Venkatesh (International Journal of Scientific Research in Civil Engineering, 2023)
Mechanical sealant for cable sleeves is a type of material or device that prevents the ingress of water, gas, or other contaminants into cable joints, terminations, or conduits. Mechanical sealant can also provide mechanical protection, fire resistance, and electrical insulation for cables and pipes. There are various types of mechanical sealant for cable sleeves, such as rubber gaskets, metal clamps, plastic plugs, or epoxy resin. Some of the factors that affect the performance and selection of mechanical sealant for cable sleeves are the type and size of the cable or pipe, the environmental conditions, the installation method, and the cost. This paper reviews the current state of the art of mechanical sealant for cable sleeves and compares the advantages and disadvantages of different sealing solutions. The paper also discusses some of the challenges and future directions for the development of mechanical sealant for cable sleeves.